2021
DOI: 10.17957/ijab/15.1728
|View full text |Cite
|
Sign up to set email alerts
|

DNA Fingerprinting and Genetic Diversity Assessment of GM Cotton Genotypes for Protection of Plant Breeder Rights

Abstract: DNA fingerprinting is rapid, easy, and efficient method for discrimination, identification and characterization of various genotypes for protection of plant breeder’s rights (PBRs). Present study was designed for DNA fingerprinting and genetic diversity assessment of 25 GM cotton genotypes (possessing Cry1Ac gene) using 297 SSR markers through conventional PCR and Polyacrylamide gel electrophoresis. Out of 297 SSR markers, 25 markers were not amplified, 28 were monomorphic and 244 were polymorphic. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
3
5
0
Order By: Relevance
“…Genome-wide allelic variation Among 300 SSR markers, 30 markers were not amplified whereas 32 were monomorphic and the remaining 208 were polymorphic in this experiment. We found only 69% of the markers revealing polymorphism among studied genotypes which is comparable to previous reports [3,5]. A total 208 polymorphic SSR markers were selected for genomewide allelic variation, among which 104 were present at the A and D, genomes, respectively.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Genome-wide allelic variation Among 300 SSR markers, 30 markers were not amplified whereas 32 were monomorphic and the remaining 208 were polymorphic in this experiment. We found only 69% of the markers revealing polymorphism among studied genotypes which is comparable to previous reports [3,5]. A total 208 polymorphic SSR markers were selected for genomewide allelic variation, among which 104 were present at the A and D, genomes, respectively.…”
Section: Resultssupporting
confidence: 88%
“…The mean values and SE values propose that there is great genetic diversity at SSR loci among studied germplasm. In current study of private alleles were found in this study (number of alleles unique to a single population), which is similar to the previous study [5,22].The maximum mean values of gene diversity was identified in the D genome followed by A-genome, suggesting that the D-genome showed more variation and the existence of genetic diversity in cotton germplasm. Further the mean values of total number of alleles per marker in the Bgenome exhibited the maximum genetic diversity as compared to the Dgenome followed by A-genome which showed the minimum genetic diversity.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations